Comment: Kraus and Sick Paper - Feiger, George (Journal of Financial and Quantitative Analysis, 1979)
George Feiger, Comment: Kraus and Sick Paper, The Journal of Financial and Quantitative Analysis, Vol. 14, No. 4, Proceedings of 14th Annual Conference of the Western Finance Association, June 21-23, 1979 (Nov., 1979), pp. 715-716